Primary clinical care series. (Park Lane, Sandown Heinemann Publishers(Pty) Ltd, 2001)
Respiratory disease, Cardiovascular disease, Gastrointestinal disease, Genitourinary disease, Primary eye care.
Keywords: Primary health care. -- Handbooks, manuals, etc; Clinical medicine -- Handbooks, manuals etc; Preventive medicine -- Handbooks, manuals, etc